ANALYSIS OF INTERNATIONAL TRADE LAW IN THE WORLD TRADE ORGANIZATION (CASE STUDY OF THE BAN ON THE EXPORT OF INDONESIAN NICKEL ORE TO THE EUROPEAN UNION) - Dodi Sugianto (Jurnal Scientia, 2023)
In a lawsuit filed with the World Trade Organization (WTO) in November 2019, the European Union argued that the ban on exports of raw materials from Indonesia had unfairly harmed the stainless steel industry on the Blue Continent. Starting in the first quarter of 2020, the export of nickel ore is banned in Indonesia. The lawsuit was filed with the Dispute Settlement Body (DSB), because Indonesia was considered detrimental to the European Union's stainless steel industry and violated the provisions of Article X:1 GATT 1994, Article XI:1 GATT 1994, and Article 3.1(b) ASCM. Based on this background, the author wants to conduct research entitled "Analysis of International Trade Law in the World Trade Organization (Case Study of the Prohibition of Indonesian Nickel Ore Exports to the European Union "). The research method used is normative juridical. The results suggest that the prohibition of nickel ore exports to The European Union resulted in the filing a lawsuit against Indonesia. After going through the dispute resolution process, Indonesia was declared defeated. The appeal process was carried out to fight the decision of the WTO dispute settlement agency, which stated that Indonesia lost the lawsuit. Indonesia remains with its stance to develop nickel downstream as an effort to increase the value nickel economy.